Rosai-Dorfman disease of the pericardium: a case report and review of literature - Lao, I-Weng (e-Century Publishing Corporation, 2014)
Rosai-Dorfman disease (RDD) is an uncommon histiocytic disease of unknown etiology. It typically presents as massive lymphadenopathy with a predilection for the cervical lymph nodes of children and young adults. However, extranodal involvement is not uncommon and may cause confusion with other neoplasms or reactive disease. We describe here a unique case of extranodal RDD manifesting as a pericardial mass in a 69-year-old man. The lesion was detected by computed tomography during a periodic examination of the chest. Subsequently positron emission tomography scan showed mild increase of flurodeoxyglucose uptake. Clinically, it was supposed to be a mesothelioma. Histological examination showed the typical features of RDD confirmed by the staining of S100 protein, which highlighted the emperipolesis of the characteristic histiocytes. To the best of our knowledge, pericardial RDD represents an extremely rare condition and should be included in the differential diagnosis of pericardial neoplasms.